2002
DOI: 10.1097/00005373-200207000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Lower Spine after Blunt Trauma Using Abdominal Computed Tomographic Scanning Supplemented with Lateral Scanograms

Abstract: Our CT + S protocol (axial CT images plus AP and lateral scanograms) outperformed screening CLSRs in the detection of fractures of the lower spine (TLJ + LS) after blunt trauma. In addition, scanogram imaging is less dependent on body habitus and adds no additional cost or time to abdominal and pelvic CT scanning. Further study is required to determine whether CT + S can routinely replace conventional radiographs of the lower spine after blunt trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7] Our study corroborates these findings, demonstrating 100% sensitivity of SCT in the detection of spine fractures at all levels, compared with 70% for PFR. Although many fractures undetected by PFR may be of minimal clinical significance, 1 of 5 patients in this series required specific treatment for a potentially unstable spine fracture.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Our study corroborates these findings, demonstrating 100% sensitivity of SCT in the detection of spine fractures at all levels, compared with 70% for PFR. Although many fractures undetected by PFR may be of minimal clinical significance, 1 of 5 patients in this series required specific treatment for a potentially unstable spine fracture.…”
Section: Discussionsupporting
confidence: 87%
“…Although recent evidence suggests that SCT has distinct advantages in the initial imaging of the spine, few studies have investigated the differences between SCT and plain radiography (PFR) for spinal imaging from a comprehensive practice-based perspective. [1][2][3][4][5][6][7][8][9] Our adult trauma center instituted a practice guideline in 2000 that called for SCT as the initial screening imaging technique for patients at risk for spinal injury. 10 SCT remained the primary modality for imaging the abdomen in hemodynamically stable patients and chest SCT was used with increasing frequency.…”
mentioning
confidence: 99%
“…Some studies only reported results for the diagnostic accuracy of the clinical features in those patients who were evaluated with the reference standard, and excluded those patients who were not [28,32,36,38]. All studies used x-ray as the reference standard for detecting vertebral fracture, although some included the use of additional imaging procedures, for example, computed tomography [35,37,39].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In our study, sensitivity of direct radiogram was 51%, therefore diagnosis of fracture could only be made with CT that was performed after direct radiograms were obtained in 49% of the patients. Regarding the sensitivity of X-ray radiography, previous studies have reported rates ranging from 33% to 74% [21][22][23][24] . The different ratios between reports may be due to the different number of patients and vertebral fractures between studies, and it may also be stem from using various types of CT scans in these studies.…”
Section: Wang Et Almentioning
confidence: 99%